Lie-algebraic structure of integrable nonlinear dynamical systems on extended functional manifolds - Pritula, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider the general Lie-algebraic scheme of construction of integrable nonlinear dynamical systems on extended functional manifolds. We obtain an explicit expression for consistent Poisson structures and write explicitly nonlinear equations generated by the spectrum of a periodic problem for an operator of Lax-type representation.